Actividades de la Asociación de Jóvenes Geógrafos de Madrid. - Barral González, Luis Miguel; Pumares Fernández, Pablo; Redondo Arandilla, Manuel (Anales de Geografía de la Universidad Complutense, 1990)
Sin resumen